Cardiovascular comorbidities antedating the diagnosis of rheumatoid arthritis. Issue 11 (23rd November 2012) - Kerola, Anne M; Kerola, Tuomas; Kauppi, Markku J; Kautiainen, Hannu; Virta, Lauri J; Puolakka, Kari; Nieminen, Tuomo V M
Abstract : Objectives: To assess the prevalence of coronary heart disease (CHD) and chronic hypertension among patients with rheumatoid arthritis (RA) at the time of diagnosis, in comparison with age-specific and sex-specific non-RA subjects. Furthermore, the impacts of age at the onset of RA, as well as gender and the presence of rheumatoid factor (RF) on the risk of these comorbidities, were evaluated. Methods: A cohort of 7209 RA patients diagnosed between January 2004 and December 2007 was identified, based on a Finnish nationwide register on special reimbursements for medication costs. The presence of CHD and chronic hypertension antedating the diagnosis of RA was identified from the same register. The prevalence of the cardiovascular comorbidities was compared with the general Finnish population, and a standardised rate ratio (SRR) for both these cardiovascular diseases was calculated. Results: The risk of having CHD at RA diagnosis was slightly elevated, the SRR being 1.10 (95% CI 1.01 to 1.20). Younger age at the onset of RA seemed to be related with higher SRR for CHD. In a subset analysis, an increased prevalence of hypertension (SRR 1.19, 95% CI 1.10 to 1.30) and CHD (SRR 1.15, 95% CI 1.00 to 1.32) was apparent only among the RF negative RA cases. Conclusions: The SRR for CHD is augmented in RA patients already at disease onset, and more pronouncedly in early onset RA. The findings highlight the importance of early prevention of atherosclerosis, regardless of RF status.